Determination of permeability characteristics of solid/liquid separation using simplex algorithm - Tanaka, Takanori; Kato, Hiroki; Fukuyama, Ryo; Hayashi, Natsuko; Jami, Mohammed Saedi; Iwata, Masashi (2013)

(untitled)
Solid/liquid separation (filtration, sedimentation, expression and centrifugation) is accompanied by liquid flow through particulate layer. Permeability data (the relationship between local specific flow resistance α and void ratio e of particulate layer) are the most important information for the analysis of a solid/liquid separation; i.e. the accurate and reliable measurement of permeability is needed for the rigorous analysis. This study investigates the determination method for permeability data of solid/liquid systems using expression data and a simplex algorithm. This methodology is a kind of curve fitting analysis for constant-pressure expression. The details of determination method for permeability data are as follows. (i) The functional form is defined as follows: α = α1e- where α1 and  are empirical constants. (ii) The initial values of α1 and  are fixed. (iii) The optimum values of α1 and  are searched by fitting theoretical time course of constant-pressure expression with experimental expression data by algorithm of simplex method. For efficacy evaluation of this estimation method, the permeability data of zinc oxide were determined using the method. The estimation shows a satisfactory agreement with the experimental results obtained from a compression-permeability test. The use of this method is of value in determining the permeability characteristics of gelatinous materials (e.g. organogel) which are difficult to measure by a conventional compression permeability test.